(untitled) (Research Journal, 2025)
Women in Nepal play a crucial role in the work place, yet they encounter numerous challenges that hinder their professional growth and well-being. Gender role has been changing in Nepali society. Traditional rigid patriarchal system has been changing gradually. Particularly urban society has realized such change. This research article has been found the problems of employed women in the study area. This research article is based on primary data which the researcher has been collected in the field survey. However, the secondary data were used in the literature review.to analyzed the current problems of the employed women. The purpose of the research is to explore major problems of employed women in the society. Exploratory and descriptive both methods were used to analysis the collected data. The result of this study shows that there is the situation of double role burden of household’s chores and income generating work of outer periphery. They are facing different physical, mental, social difficulties in both government and private sectors job. The findings of the study are Job insecurity, household’s chores, and lack of family support, difficulty in work place, future insecurity, and low wage pay in private sectors employees were the major problems of the employed women in the study area. To address these problems, the local government have to make good policies targeting the employed women which could make east to daily life a good expectation of the future.